Peran Perencanaan Pembelajaran dalam Mewujudkan Tujuan Pendidikan Berbasis Kompotensi - Rendi Rendi; Gresia Monika Sinaga; Ferdi Eka Darma; Lisna Novalia (Lembaga Pengembangan Kinerja Dosen, 2025)
This article discusses the importance of planning in the learning process, which serves as a systematic guide to achieving educational goals. Planning is an organized process and mindset that supports the effectiveness of learning implementation. Education, as a means of humanizing individuals, aims to develop the quality of human resources that are not only profession-oriented but also equipped to face life’s challenges. With a dynamic and systematic approach, education needs to adapt to the times and societal needs, including aspects of educational autonomy and character development of individuals who are faithful, responsible, and productive.This study employs a literature review method, examining relevant theories and references to provide a theoretical foundation for learning planning. The discussion highlights that learning planning, such as lesson plans, syllabi, and teaching methods, plays a crucial role in helping teachers organize learning activities effectively. Professional mentoring is one of the strategies to enhance teaching quality, foster collaboration, and build a professional learning community in schools. Therefore, effective planning, supported by teacher competence and mentoring strategies, will comprehensively improve the quality of education.